2019
DOI: 10.1002/pd.5436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medication intake in early pregnancy on the fetal fraction of cell‐free DNA testing

Abstract: Objectives:To determine the association between medications intake in early pregnancy and variation in the fetal fraction (FF) in pregnant women undergoing cell-free DNA (cfDNA) testing. Methods:We performed a retrospective cohort study of women (n = 1051) undergoing cfDNA testing at an academic center. The exposed group included women taking medications (n = 400; 38.1%), while the nonexposed group consisted of women taking no medications (n = 651; 61.9%). Our primary outcome was FF. We performed univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The FF was significantly lower in the group taking two or more drugs than in the group not taking any drugs. The group taking metformin had a 1.8% decrease in the FF (42). In addition, the FF present in blood samples taken immediately after completing a cycling exercise was significantly lower than that taken before cycling, with a decreased range of 1-17% (43).…”
Section: Maternal Characteristicsmentioning
confidence: 85%
“…The FF was significantly lower in the group taking two or more drugs than in the group not taking any drugs. The group taking metformin had a 1.8% decrease in the FF (42). In addition, the FF present in blood samples taken immediately after completing a cycling exercise was significantly lower than that taken before cycling, with a decreased range of 1-17% (43).…”
Section: Maternal Characteristicsmentioning
confidence: 85%
“…18 Nevertheless, others have shown acetyl salycillic acid or heparin did not affect FF. 19 The same study stated metformin might be correlated with lower FF. 19 Although metformin was shown to reduce the secretions leading to proliferation and metabolism, medication was not found directly associated with the FF.…”
Section: Pregnant Using Levothyroxine Sodium (N=51)mentioning
confidence: 92%
“…19 The same study stated metformin might be correlated with lower FF. 19 Although metformin was shown to reduce the secretions leading to proliferation and metabolism, medication was not found directly associated with the FF. Another repeated failed NIPT in a woman with an autoimmune disease case demonstrated the patient taking acetyl salycillic acid, prednisolone, and LMWH.…”
Section: Pregnant Using Levothyroxine Sodium (N=51)mentioning
confidence: 92%
“…However, with the rapid expansion of non-invasive, cell-free fetal DNA testing,134 single gene or multiple gene PGx panel testing may be possible in the near future. Some data have indicated that maternal medication use may impact the quantity of cell-free fetal DNA available 135…”
Section: Weighing the Benefits And Risks Of Pgx Testing In Childrenmentioning
confidence: 99%